Dynamics of pine hawkmoth (Hyloicus pinastri L.): Search for stationary dynamical regime - L.V. Nedorezov (Computational Ecology and Software, 2013)
In current publication possible population dynamics regimes are analyzed using pre-model statistical method. Method was applied to well-known pine hawkmoth (Hyloicus pinastri L.) time series (Schwerdtfeger, 1944, 1968). Provided statistical analysis showed that observed dynamics of pine hawkmoth doesn't correspond to strong 2-, 3-,..., or 9-year cycles which can be generated by one-dimensional discrete models, and doesn't correspond to fluctuations near stable level.